COHERENT BACKSCATTERING OF ACOUSTIC WAVES IN THE NEAR FIELD - Margerin L.; Campillo M.; Van Tiggelen B.A. (My University, 2001)
Recent studies have shown that interference plays an important role in various phenomena observed for waves propagating through random media. Among these phenomena, the so-called cone of coherent backscattering has received much attention in optics. In this paper, we study analytically and numerically the coherent backscattering of acoustic waves in a seismological context. In particular, we focus on the near-field detection of scattered waves and the effect of transient sources. We show that interference results in an increase of the coda intensity as compared to the prediction of radiative transfer theory. After a transient regime, a spot of backscattering enhancement stabilizes in a sphere of radius half a wavelength centred at the source of seismic waves. Several effects such as absorption, boundary conditions and scattering anisotropy are investigated. Our study demonstrates the robustness of coherent backscattering and may offer a possible means of discriminating single versus multiple scattering in the observed coda.